Pemanfaatan RinfoSheet Sebagai Media Informasi Laporan Penjualan Barang pada Raharja Internet Cafe - Untung Rahardja; Eka Purnama Harahap; Dini Intan Pratiwi (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2018)
Raharja Internet cafe (RIC) is a service place at Perguruan Tinggi Raharja which is dedicated to help the lecture activities of Perguruan Tinggi Raharja Students. Reports on the sale of goods on the RIC is information that is needed for smooth business. But RIC still uses Microsoft Excel to do input reporting, which report can not be saved automatically to enable the data being input is lost, then when will give sales report to the manager must be printed / printout first, of course this is not effective because it will lead to paper buildup. Therefore, it is necessary to use RinfoApps RinfoSheet, a number and data processing facility where users are able to create and share data on the web and can be accessed anywhere and anytime, either via computer, smartphone or tablet. In this research, found 2 (two) problems in the existing system and supported by 4 (four) research method that is observation method, analysis, literature study and implementation. The final result of the research is making the sales report can be done online and the report will be stored automatically, and can be shared so it does not need to print reports to be given to the manager.